Meningkatkan Minat Berkunjung Kembali melalui Kepuasan Konsumen sebagai Variabel Intervening pada Pengunjung Domestik Wisata Puncak Becici Yogyakarta - Siti Malikhah; Muinah Fadhilah; Henny Welsa (Universitas Batanghari, 2023)
The purpose of this study was to analyze the effect of destination image, facilities and purchase experience to customer satisfaction partially; the effect of destination image, facilities, purchase experience and customer satisfaction to revisit intention partially; to analyze whether customer satisfaction is able to mediate the relationship between destination image, facilities and purchase experience with revisit intention. This research was located in Bantul Regency at the Tour Becici Peak, Yogyakarta. The number of samples as many as 200 respondent which is domestic visitor at the Tour Becici Peak, Yogyakarta. Data analysis used in this research were descriptive analysis, inferensial analysis, and mediation analysis. The analysis tool in this research was the Partial Least Square (PLS) analysis with SmartPLS 3.2.9 software, and the mediation analysis used the Bootstrapping. The results of the analysis on hypothesis testing in this study indicate that destination image and purchase experience has a positive and significant effect to customer satisfaction partially; facilities haven’t effect to customer satisfaction partially; destination image, facilities, purchase experience and customer satisfaction has a positive and significant effect to revisit intention partially. The results of the bootstrapping test on mediation analysis show that customer satisfaction is able to mediate destination image and purchase experience with revisit intention; customer satisfaction is unable to mediate facilities with revisit intention.